A patient with dextrocardia and chagas disease: case report and literature review - Julián Felipe Porras-Villamil; Mario Javier Olivera (Case Reports)
Introduction: About half a million patients in Colombia are currently infected with Trypanosoma cruzi. However, little is known about patients with Chagas disease and anatomical defects such as dextrocardia.